Lover - Harris, Bertha, 1937- (Cutting edge (New York, N.Y.), 1993)
A landmark work of lesbian literature, Lover was first published in 1972 by the now-defunct feminist press, Daughters, to tremendous critical acclaim. Emerging out of the women's and gay liberation movement alongside the early work of such writers as Rita Mae Brown and Jill Johnston, the novel features fictional and historical characters who run the gamut from saint to poor white trash, and who are by turn vulnerable and strong. One of the finest examples of early post-Stonewall lesbian fiction, Lover is poised to entice a new generation of readers. In this new edition, Harris reintroduces her work, providing engaging background on the cultural and personal milieu in which it was produced and painting a scathing and witty picture of the book's original publisher. Revealing the real-life personalities behind some of the novel's characters, the introduction is an amusing retrospective sure to entertain those who remember the heady post-Stonewall days, and to enlighten younger readers.